Evaluation of anatomoradiological findings on trigeminal neuralgia patients using computed tomography and cone-beam computed tomography - Aksoy, Seçil; Sayın Şakul, Arzu; Görür, Durmuş İlker; Şakul, Bayram Ufuk; Orhan, Kaan (Multidisciplinary Digital Publishing Institute(MDPI), 2022)
The study aimed to establish and evaluate anatomoradiological landmarks in trigeminal neuralgia patients using computed tomography (CT) and cone-beam CT. CT images of 40 trigeminal neuralgia (TN) and 40 healthy individuals were retrospectively analyzed and enrolled in the study. The width and length of the foramen rotundum (FR), foramen ovale (FO), foramen supraorbitale, and infraorbitale were measured. The distances between these foramen, between these foramen to the median plane, and between the superior orbital fissure, FO, and FR to clinoid processes were also measured bilaterally. Variations were evaluated according to groups. Significant differences were found for width and length of the foramen ovale, length of the foramen supraorbitale, and infraorbitale between TN and control subjects (p < 0.05). On both sides, FO gets narrower and the length of the infraorbital and supraorbital foramen shortens in the TN group. In most of the control patients, the plane which passes through the infraorbital and supraorbital foramen intersects with impression trigeminale; 70% on the right-side, and 67% in the left-side TN groups. This plane does not intersect with impression trigeminale and deviates in certain degrees. The determina-tion of specific landmarks allows customization to individual patient anatomy and may help the surgeon achieve a more selective effect with a variety of percutaneous procedures in trigeminal neuralgia patients.
Keywords: CBCT; CT; Foramen Ovale; Foramen Rotundum; Impressio Trigeminale; Trigeminal Neuralgia